Собачья работа: [роман] / Л. Н. Пучков - Пучков Лев Николаевич (Черная кошка, 1998)
Экземпляры: аб (20200206) / Инвентарный номер: 54846 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: П 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6